Distribution of cortical granules and meiotic maturation of canine oocytes in bi-phasic systems - Apparicio, Maricy [UNESP]; Mostachio, Giuliano Q. [UNESP]; Motheo, Tathiana F. [UNESP]; Alves, Aracelle E. [UNESP]; Padilha, Luciana [UNESP]; Pires-Butler, Eliandra A. [UNESP]; Savi, Paula A. P. [UNESP]; Uscategui, Ricardo A. R. [UNESP]; Luvoni, Gaia C.; Vicente, Wilter R. R. [UNESP] (CSIRO Publishing, 2015)
The aim of this study was to evaluate the influence of different bi-phasic systems with gonadotrophins and steroids on in vitro maturation rates of oocytes obtained from bitches at different reproductive stages (follicular, luteal, anoestrous). In System A (control) oocytes were matured for 72h in base medium (BM) with 10IUmL-1 human chorionic gonadotrophin (hCG), 1gmL-1 progesterone (P4) and 1gmL-1 oestradiol (E2); in bi-phasic System B oocytes were matured for 48h in BM with hCG and for 24h in BM with P4; in bi-phasic System C oocytes were matured for 48h in BM with hCG, P4 and E2, and for 24h in BM with P4; in System D, oocytes were cultured in BM without hormonal supplementation. Data were analysed by ANOVA. There was a positive effect of the bi-phasic systems on germinal vesicle breakdown, metaphase I and metaphase II rates, irrespective of reproductive status (P<0.05). Bi-phasic systems were also beneficial for cortical granule distribution (an indication of cytoplasmic maturation) and its relationship to nuclear status: 74.5% of the oocytes cultured in System B and 85.4% of those cultured in System C presented both nuclear and cytoplasmic maturation (P<0.001). The stage of the oestrous cycle did not influence maturation rates.
Keywords: hormones; in vitro maturation